Novel variants in SPTAN1 without epilepsy: An expansion of the phenotype. Issue 12 (11th December 2018) - Gartner, Valerie; Markello, Thomas C.; Macnamara, Ellen; De Biase, Andrea; Thurm, Audrey; Joseph, Lisa; Beggs, Alan H.; Schmahmann, Jeremy D.; Berry, Gerard T.; Anselm, Irina; Boslet, Emma; Tifft, Cynthia J.; et al.
Abstract : We describe two unrelated children with de novo variants in the non‐erythrocytic alpha‐II‐spectrin ( SPTAN1 ) gene who have hypoplastic brain structures, intellectual disability, and both fine and gross motor impairments. Using agnostic exome sequencing, we identified a nonsense variant creating a premature stop codon in exon 21 of SPTAN1, and in a second patient we identified an intronic substitution in SPTAN1 prior to exon 50 creating a new donor acceptor site. Neither of these variants has been described previously. Although some of these patients' features are consistent with the known SPTAN1 encephalopathy phenotype, these two children do not have epilepsy, in contrast to reports about nearly every other patient with heterozygous SPTAN1 variants and in all patients with a variant near the C‐terminal coding region. Moreover, both children have abnormal thyroid function, which has not been previously reported in association with SPTAN1 variant. We present a detailed discussion of the clinical manifestations of these two unique SPTAN1 variants and provide evidence that both variants result in reduced mRNA expression despite different locations within the gene and clinical phenotypes. These findings expand the motor, cognitive, and behavioral spectrum of the SPTAN1 ‐associated phenotype and invite speculation about underlying pathophysiologies.